Emerging trends and advancements in the processing of dairy whey for sustainable biorefining - Goyal, Chhaya; Dhyani, Priya; Rai, Dinesh Chandra; Tyagi, Swati; Dhull, Sanju Bala; Sadh, Pardeep Kumar; Duhan, Joginder Singh; Saharan, Baljeet Singh (Hindawi Limited, 2023)
Increased milk production has boosted the market of milk-driven products, and as a result, the by-product production has also increased, which is a challenge to dispose of. Whey, a cheese by-product, is also increasing yearly, and its disposal in water bodies is responsible for water pollution and thus is an issue for the dairy sector. In this context, extensive research has been going on to valorize this by-product and create alternative ways to remove the organic load in whey rather than disposing of it. Recently, exciting developments have been made to convert whey into value-added commodities such as biofuels (bioethanol, biodiesel, and biohydrogen), bioplastics, bacterial cellulose, food colors and flavors, bioprotective solutions, bioactive peptides, and single-cell proteins. In this review, we aim to comprehend the recent developments and challenges in producing a whole range of value-added ingredients with whey as feedstock through microbial fermentation. Particular focus was paid to the potential of novel genetically engineered or adapted microbial strains to valorize bovine whey economically and sustainably.